(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This research presents the results of laboratory experiments conducted to evaluate the thermal properties of a copper heat pipe operating in water and anti-freezing liquid under various angles and filling ratios. The method of designing experience in experiments is the method of Taguchi. Experiments were conducted in 9 options, and in options 4 and 8, it was determined that the temperature of the condensate-forming part of the heat pipe was 100-120°C. Therefore, in these options, more heat can be accumulated than in other options, and in these options, phase change materials with a high melting temperature can be used as a heat accumulating material.